2010
DOI: 10.1590/s0103-50532010000600023
|View full text |Cite
|
Sign up to set email alerts
|

Iridoids from Hymenodictyon floribundum

Abstract: Das cascas do tronco e das folhas do Hymenodictyon floribundum B. L. Rob foram isolados dois novos iridoides, floribundano A (1) e floribundano B (2), e três compostos conhecidos, lupenona (3), escopoletina (4) e 4,5-di-hidroblumenol A (5). As estruturas de todos os compostos foram estabelecidas com base nos seus dados espectroscópicos.Two new iridoids floribundane A (1) and floribundane B (2) and the known compounds lupenone (3), scopoletin (4) and 4,5-dihydroblumenol A (5) were isolated from trunk bark and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 18 publications
(26 reference statements)
0
4
0
1
Order By: Relevance
“…Valeriana jatamansi (Valerianaceae) 53) 119. Jatamanvaltrate 12.6, 6.6, H-6), 2.08 (dd, 12.6, 10.2, H-6), 4.83 (dd, 10.2, 6.6, H-7), 2.88 (d, 2.4, H-9), 4.28 (d, 12.6, H-10 57) 126. ; structure confirmed by X-ray study. Triosteum himalayanum (Caprifoliaceae), 58) T. pinnatifidum 59) 127.…”
Section: Versibirioside (6-o-[3љ-(e)-cinnamoyl-a-l-rhamnopyranosyl]-gunclassified
“…Valeriana jatamansi (Valerianaceae) 53) 119. Jatamanvaltrate 12.6, 6.6, H-6), 2.08 (dd, 12.6, 10.2, H-6), 4.83 (dd, 10.2, 6.6, H-7), 2.88 (d, 2.4, H-9), 4.28 (d, 12.6, H-10 57) 126. ; structure confirmed by X-ray study. Triosteum himalayanum (Caprifoliaceae), 58) T. pinnatifidum 59) 127.…”
Section: Versibirioside (6-o-[3љ-(e)-cinnamoyl-a-l-rhamnopyranosyl]-gunclassified
“…Twenty compounds were isolated from the EtOAc fraction by silica gel column chromatography and normal-phase, semi-preparative, high-performance liquid chromatography (HPLC). Among these compounds, we isolated one new iridoid, which namely neonanin C ( 1 ) (neonanin A and B have been reported in our previous study [9]), one monocyclic iridoid ring-opened derivative namely neonanin D ( 2 ), two new bis-iridoid derivatives namely reticunin A ( 3 ), reticunin B ( 4 ) and sixteen known compounds, including strychnovoline ( 5 ) [15], siphonostegiol ( 6 ) [16], isoboonein ( 7 ) [17], floribundane B ( 8 ) [18], alyxialactone ( 9 ) [19], syringaresinol ( 10 ) [20], (+)-pinoresinol ( 11 ), (+)-medioresinol ( 12 ) [21], 4-methoxycatechol ( 13 ) [22], protocatechuic acid ( 14 ) [23], trans -caffeic acid ( 15 ) [24], syringic acid ( 16 ) [25], 3-hydroxy-1-(4-hydroxy 3,5-dimethoxyphenyl)-1-propanone ( 17 ) [26], ferulic acid ( 18 ) [27], protocatechuic acid methyl ester ( 19 ) [28], C-veratroylglycol ( 20 ) [29]. The structures of the new compounds were determined through spectral analyses, including IR, UV, 1D- and two-dimensional (2D)-NMR, as well as HR-ESI-MS data.…”
Section: Resultsmentioning
confidence: 99%
“…Natural molluscicidal compounds isolated from a large number of plants have received much attention in hope that they might provide cheap, biodegradable and effective control agents in rural areas where schistosomiasis is endemic. 8,9 As part of our ongoing study of the plants of Angola, 2,10,11 we observed that Euphorbia conspicua latex exhibits strong molluscicidal activity 2 and may be a potential source of bioactive compounds. This work intended to isolate and describe the constituents of the active fractions and to evaluate their effects.…”
Section: Introductionmentioning
confidence: 93%